Evaluasi Pelayanan Penumpang (Studi Kasus: Pelabuhan Dili Timor Leste) - Ni Luh Made Ayu Mirayani Pradnyadari; I Wayan Gede Darma Yoga; Julia Maria Granadeiro Goncalves (Universitas Pendidikan Nasional, 2022)
Timor-Leste as a new country has various efforts to advance the country itself, one of which is the achievement is to build several ports in three locations, because for the time being it still mandates one port located in the center of Dili city, namely;